Some Aspects of Secular Trend - Povilonis, Salezijus (Problemos, 1968)
Secular trend of human development is displayed as acceleration of development in childhood, as prolongation of life and its active period in particular, as changes in human pathology. Secular trend is distinctly revealed among population of Lithuanian SSR. Improvement of nutrition and decrease of sickness rate, as a result of positive changes in social environment, are pointed as factors of secular trend. Secular trend manifestations are evaluated as a complex of environmental modifications that may fluctuate in the plasticity limits of heredity. Secular trend is extending, since there in a great reserve for progress in a field of human physical appearance. Regarding to possibilities, presented by science, secular trend would have to lead to the optimal modifications of human organism.